Exploring factors contributing to Irregular cross-border movement into South Africa - Mabeba, Bernard (My University, 2021)
This study examines the factors contributing to irregular human cross-border movement into South Africa and uses the Beitbridge Border Post in Limpopo, South Africa, as a case study. The study also looks at the effectiveness of mechanisms the country has put in place to address such irregular border crossings. The study found that the main contributing factors to high levels of irregular cross-border movement into South Africa include corruption, poor infrastructure, poor working conditions as well as poor economic conditions in neighbouring countries. Existing literature on the subject indicates that most research on factors contributing to irregular cross-border movements focusses mainly on the push and pull factors in sending and receiving countries, respectively. Not much scholarly attention has been paid to factors relating to border control mechanisms that states or regional bodies put in place to address irregular border crossings. By identifying inefficiencies in South Africa’s border control mechanisms, the research is a step towards filling this knowledge gap
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Migration and Displacement, at the Faculty of Humanities, University of the Witwatersrand, 2021